Vascular endothelial growth factor expression in renal cell carcinoma - Mohtarrudin, Norhafizah; Mhd Nasir, Mhd Shidee; Abu Bakar, Rosila; Koey, Peng Mun; Osman, Malina; Mohd Yusoff, Suryati (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Renal cell carcinoma (RCC) is the most common renal malignancies. In advanced stage, it is highly resistant to systemic therapies. RCC is a highly vascular tumour and angiogenesis pathway has been postulated in its carcinogenesis. Novel drug targeting Vascular Endothelial Growth Factor (VEGF) and advanced surgical interventions have shown to increase the overall patients’ survival. In this study, we evaluated the VEGF expression of RCC using immunohistochemistry technique and its potential correlation with the tumour grades. Methods: 40 RCC cases that underwent nephrectomy were selected. The archived samples of formalin fixed, paraffin-embedded (FFPE) were retrieved. The tumour tissue blocks were carefully chosen, sectioned and stained with VEGF using immunohistochemistry technique. The intensity of VEGF expression was scored as 0 (negative), 1+ (weak), 2+ (moderate) or 3+ (strong). Results: Majority of the RCC cases were male, with male to female ratio of 2.1:1. Mean patient age was 56.2 years (age ranged between 16 to 74 years). Most of the cases were Malays (42.5 %). VEGF was expressed in 36 (90%) of RCC cases. Among the 36 cases that were immunopositive, 8 (16.7%) were grade 1, 20 (55.6%) grade 2 and 8 (16.7%) grade 3. There was no significant association between VEGF expressions score and grades of RCC (p=0.39). Conclusion: VEGF was expressed in majority of RCC cases although there was no significant association with tumour grades.